Potensi Implementasi Science, Technology, Engineering, Art And Mathematic (Steam) pada Pembelajaran IPA Materi Perubahan Iklim Ditinjau dari Prespektif Guru IPA Se Kabupaten Demak - Priyono, Slamet; Nugroho, Ary Susatyo; Roshayanti, Fenny (PGRI Kota Semarang, 2024)
This article aims to determine the profile of junior high school science teachers in the potential for implementing the STEAM learning approach to the concept of climate change to improve the creative thinking skills of junior high school students in Demak Regency. STEAM learning is a learning approach that emphasizes the relationship between knowledge and skills in science, technology, engineering, art and mathematics. This research is a type of qualitative descriptive research involving 19 junior high school science teachers in Demak Regency. The instrument is a questionnaire given online via Google Form. The research results showed that 52.6% of teachers knew the STEAM learning approach and 47.4% did not know. As many as 26.3% of teachers already understand learning with STEAM projects and only 57.1% have implemented it, while 42.9% have not implemented it. The results showed that 48% had great fun and 52% enjoyed learning with the STEAM approach and 42.1% of students became very active, 57.9% of students became active.